Why states rebel: understanding state sponsorship of terrorism - Kirchner, Magdalena (2014)
State Sponsorship of Terrorism connects three major contemporary issues of international relations: intrastate conflict, third-party intervention, and interstate relations. In order to understand,why states choose not to fight but to form alliances with terrorist organizations, the study links international and domestic security challenges and policy incentives with formal and informal limitations political leaders have to take into consideration when adjusting to them. In this study, it is argued in a neoclassical realist tradition of international relations theory that sponsorship emerges under specific conditions of mutually reinforcing external and internal security dilemmas, constituting a third way between balancing a rival through interstate alliance formation or armament. Hence, the study traced both extent and shape of sponsorship policy back to specific interplay patterns between interstate enmity and domestic challenges to the political leadership. Examining Syria’s relations with Palestinian Fatah, Turkish-Kurdish PKK, and Lebanese Hizballah, between 1964 and 2006, the analysis explored the formation and developmentof sponsorship patterns in order to gain a deeper understanding of a process, which had not yet been systematically traced.
Keywords: Partiya Karkerên Kurdistan; Ḥizb Allāh; Ḥarakat at-Taḥrīr al-Waṭanī al-Filasṭīnī; Syrien; Israel; Türkei; Hochschulschrift